The determination of caffeine content in tea using headspace solid phase microextraction (HS-SPME) and gas chromatography-mass spectrometry (GC-MS) / Nur Amirah Mokhtar - Mokhtar, Nur Amirah (2015)
This study was conducted to determine the caffeine content in different types and brands of tea which are black tea, oolong tea and green tea and to identify the major volatile compounds present in those tea by using headspace-solid phase microextraction (HS-SPME) with gas chromatography-mass spectrometry (GCMS). About 1 g of dry tea leaves from tea samples were extracted by using polydimethylsiloxane/divinylbenzene (PDMS/DVB) fiber at 50 °C for 40 min. The quantification of caffeine was calculated based on calibration curve of standard caffeine. The result shows that green tea has the highest amount of caffeine, followed by oolong tea and black tea. While in the analysis of four brands of black tea, brand D has the highest caffeine content, followed by brand C, brand B and brand A. The major volatile compounds present in black tea, oolong tea and green tea are benzaldehyde, D-limonene, cyclopentasiloxane, methyl salicylate, tetradecane and caryophyllene. In this study, D-limonene is only present in green tea. Therefore, it can be used as the reference volatile compound to differentiate between unfermented green tea and fermented tea such as black tea and oolong tea.